Laboratory Bioassays on the Susceptibility of Trimen’s False Tiger Moth, Agoma trimenii (Lepidoptera: Agaristidae), to Entomopathogenic Nematodes and Fungi - Morris, C.; Malan, A.P.; De Waal, J.Y.; Johnson, S. (South African Journal of Enology and Viticulture, 2020)
Trimen’s false tiger moth, Agoma trimenii (Lepidoptera: Agaristidae), recently developed as a pest of grapevine in the Northern Cape and Limpopo (Groblersdal area) provinces of South Africa. Little is known about the biology of A. trimenii and control options are lacking. The aim of this study was to test the susceptibility of A. trimenii larvae and pupae to two locally isolated entomopathogenic nematodes (EPNs), Steinernema yirgalemense and Heterorhabditis noenieputensis, and two commercially available entomopathogenic fungi (EPF), Metarhizium anisopliae and Beauveria bassiana, under laboratory conditions. Larvae and pupae were screened for pathogenicity of the two nematode species, using a concentration of 100 infective juveniles (IJs)/50 μl of water. After 48 h, 100% mortality of the larval stage was found. However, no pupae were infected with EPNs. Larvae and pupae were screened for pathogenicity of the two EPF isolates by means of a dipping test, at a concentration of 0.2 ml/500 ml water and 0.5 g/500 ml water, respectively. Five days post-treatment, 100% larval mortality was recorded in comparison with no deaths in the controls. Overt mycosis was only observed in the case of M. anisopliae. However, in the case of pupae, no mortality was observed for both the nematode and the fungal applications. In future studies, the prepupal soil stage of A. trimenii should be screened for susceptibility to EPNs and EPF. The results of this study indicate the excellent potential of EPNs and EPF as biological control agents against the larvae of A. trimenii, especially for application to small areas with high infestation, without disrupting an integrated pest management programme.